The Formation of Historical Thought: Didactics, Dispute and Democracy. Interview with Dr. Antoni Santisteban - Ramos Torres, Yeimer Gerardo (2024)
This article transcribes an extract from program nº 109 of the ninth season of the Huellas podcast: social studies with critical thinking; an interview is conducted with Dr. Antoni Santisteban Fernández, who is a researcher and teacher in History Didactics at the Autonomous University of Barcelona, Catalonia, Spain. The concepts of historical thought, the competencies and/or abilities that converge in their didactic process are addressed. In addition, the conflictive and dispute dimension involved in the teaching of history, social sciences and, in the Costa Rican case, social studies in secondary education is discussed. Finally, the repercussions of the didactics of social sciences in the democratic processes in the construction of a citizenry committed to social justice, equity and equality are analyzed.